KESIAPSIAGAAN DESA TERHADAP BENCANA TANAH LONGSOR - Linda Octavia; Eko Prawoto (ATRIUM: Jurnal Arsitektur, 2018)
Title: Village Preparedness Against Landslide Disaster Disasters that have previously occurred can almost be guaranteed that they would most likely reoccur without our knowing when and where they would take place once again. Maximum preparation and understanding about what we should do during events of disaster are substantial measures that we must take. In addition, knowledge or experiences relating to disasters should also be passed down to the next generation. This study employed methods of in-depth interviews and direct observations to acquire data regarding indicators of disasters found in the village of Kebonharjo. The interviews were performed with the villagers, while observations were carried out in a number of locations where landslides had occurred. The acquired results were subsequently analyzed in order to gain an understanding of the most significant indicators that can be used as a standard for the villagers to be prepared in the event of a disaster. The availability of written knowledge and documentation pertaining to these indicators will consequently lead to such knowledge being more widely known by the community and they can also serve as a useful resource for the villagers when they find locations that are considered to show indications of disaster, in which they can then make a quick identification of the situation. Transforming oral knowledge into a written one is admittedly an appropriate choice in order to strengthen the village’s preparedness against disaster.